Organizational and Cultural Change at Pump Industry in Indonesia Using SWOT Analysis for Digital Transformation Sustainability - cornelius, joseph; Muallifah, Siti; Tyas, Ari Anggarani Winadi Prasetyoning (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
This study examines the organizational and cultural transformation imperatives within Indonesia's pump manufacturing industry, focusing on the critical challenges of digitalization and sustainability in an increasingly competitive global market. Here, we investigate whether pump manufacturers can leverage digital transformation and cultural change to enhance their market position, particularly as the industry experiences robust growth driven by increasing demand for water treatment solutions and infrastructure projects. Through comprehensive SWOT analysis, this study identifies key organizational capabilities and challenges, in addressing the industry's historical reliance on imports and technological gaps. Thus, this study aims to obtain critical areas for improvement, including the necessity for systematic employee training programs to facilitate cultural adaptation and the implementation of environmentally sustainable technologies. The result shows digital transformation can enhance operational efficiency while supporting sustainability goals. Here, the recommendations for Indonesian pump manufacturers to navigate rapid global challenges, emphasizing the importance of balancing technological advancement with organizational culture change to achieve sustainable competitive advantages in the international market in near future.